The Power of Tolerance vs. Unselfishness as a Cultural Determinant of Cooperation - Eriksson, Kimmo; Simpson, Brent; Vartanova, Irina (Frontiers in Psychology, 2021)
Cooperation in collective action problems and resource dilemmas is often assumed to depend on the values of the individuals involved, such as their degree of unselfishness and tolerance. Societal differences in cooperation and cooperative norms may therefore result from cultural variation in emphasis on these personal values. Here we draw on several cross-national datasets to examine whether society-level emphasis on unselfishness and tolerance and respect for other people predict how societies vary in cooperation (in a prisoner’s dilemma) and in norms governing cooperation (in a common pool resource dilemma). The results suggest that high levels of cooperation and cooperative norms are promoted specifically by a cultural emphasis on tolerance.